Lemas e teoremas: um caminho para a consolidação de conceitos geométricos na educação básica - Freitas, Alana Paula Araújo (2016)
The purpose of this paper is to present a methodology for the Teaching of Mathematics to consolidate basic concepts of geometry significantly. Thus, relating geometric entities present in the statements of theorems with the verification thereof. It is possible to bring back the axiomatic deductive method, in the basic education geometry classes in this research with the help of educational computing and dynamic geometry software GeoGebra. For this, it was first created a roadmap for learning material that guides the verification theorem and leads to reflection of geometric definitions that can be executed with the software. Then it was held the implementation of the roadmap with a group of high school students. And finally, the analysis of the results obtained in the application was made. To learn more about the searched class and enable the comprehension of the method’s effectiveness it was applied at first a questionnaire to probe the initial condition of the students, and at a second time an interview to investigate concepts present in the questionnaire. The data analysis showed an amazing affnity of students with the verification method of theorems aided by new technologies, as well as the conceptual evolution of the involved definitions. It is believed that with the introduction of theorem demonstrations associated with computer technology in the teacher’s methodology can be a path to improvement in Geometry teaching in elementary School.